2009
DOI: 10.2190/pm.39.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity and Quality of Life in Obese Patients. Results from a Case-Control Study

Abstract: Obesity is significantly associated with a significant major risk of psychiatric comorbidity and poor quality of life; comorbid mental disorders play a significant role in worsening quality of life of obese patients; a multimodal approach to the treatment of obesity, including psychiatric evaluation and intervention, is needed to improve quality of life of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
2
15
0
7
Order By: Relevance
“…Several studies have brought awareness to the psychological comorbidity in obesity, 18 and a significant improvement in quality of life after weight-loss was also documented, especially in studies that investigated the effects of gastric bypass surgery where there is a dramatic body weight loss. 32 Table 3 depicts the significantly lower baseline scores of quality of life (D1, D2) in our study participants as compared with a healthy population reference group; but no more difference was noticed after 3 months of body weight loss intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have brought awareness to the psychological comorbidity in obesity, 18 and a significant improvement in quality of life after weight-loss was also documented, especially in studies that investigated the effects of gastric bypass surgery where there is a dramatic body weight loss. 32 Table 3 depicts the significantly lower baseline scores of quality of life (D1, D2) in our study participants as compared with a healthy population reference group; but no more difference was noticed after 3 months of body weight loss intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity with psychiatric axis I/II disorders, particularly among obese patients, was associated with lower quality of life measures on the WHOQOL-BREF questionnaire. 18 Another study also showed that an abnormally high BMI was associated with an increased likelihood of having serious psychological distress, independent of obesity-related comorbidities, lifestyle factors, or emotional support. 1921 …”
Section: Introductionmentioning
confidence: 97%
“…Первый подход подразу-мевает зависимость нарушений приема пищи от на-личия у больных ожирением сопутствующих психи-ческих расстройств [11,12,13]. При таком подходе нарушения саморегуляции рассматриваются в каче-стве одного из компонентов имеющегося у больного психического расстройства [14].…”
Section: обсуждение и заключениеunclassified
“…Dadas las anteriores conclusiones se considera necesario incluir una evaluación de carácter psicopatológico en los programas de intervención de pacientes con obesidad, y valorar consecuentemente si debe implementarse un tratamiento de orden psicológico y/o psiquiátrico según el diagnóstico resultante, sugerencia que es acorde con la propuesta de diversos autores 19,21,22,[39][40][41] . 5.…”
Section: Conclusiones Y Recomendacionesunclassified
“…En Italia 19 , se publica en 2009 un estudio que empleó 293 pacientes con obesidad y 293 personas control en normopeso, determinándose que la obesidad se asocia de manera significativa con un mayor riesgo de comorbilidad psiquiátrica y peor calidad de la vida, teniendo en cuenta los criterios DSM-IV y OMS respectivamente. También ese año, en Bélgica 20 , compararon 155 adolescentes con sobrepeso (media de edad 13,7 años) con 73 que no lo presentaban y comprobaron que el 37,5 % de los participantes en el grupo con sobrepeso cumplían los criterios DSM-IV para al menos un trastorno mental, sien- , empleando esta misma metodología, se publicó en 2007 una encuesta a 534 pacientes mujeres con sobrepeso u obesidad.…”
unclassified